2014
DOI: 10.1002/app.41045
|View full text |Cite
|
Sign up to set email alerts
|

Degradability of extruded polyethylene/chitosan blends compatibilized with polyethylene‐graft‐maleic anhydride under natural weathering

Abstract: The impact of chitosan on the natural weathering behavior of two blends obtained by mixing either polyethylene (PE) with chitosan or PE, chitosan and polyethylene‐graft‐maleic anhydride (PEgMA) as a compatibilizer is analyzed. In order to follow the weathering behavior of both the uncompatibilized and compatibilized systems, the blend films are exposed to outdoor conditions for 6 months. The weathering behavior of the films is monitored by mechanical tests, spectroscopic Fourier transform infrared, and morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Additionally, its hydrophilic character does not allow its homogeneous dispersion in the PP matrix that is hydrophobic; however, the addition of compatibilizer improved the homogeneity of the films, as shown in Figure 3(2A–2C). This behavior is consistent with the literature where it was reported that the use of polymers grafted with maleic anhydride are good compatibilizers for immiscible binary mixtures [13,14,15,16]. Moreover, films with smaller chitosan particle size (Figure 3(3A–3C)) showed better dispersion of the particles of chitosan in the PP matrix, so in these films the formation of agglomerates is almost unnoticeable, which is attributed to the good dispersion of the chitosan particles in the PP matrix.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, its hydrophilic character does not allow its homogeneous dispersion in the PP matrix that is hydrophobic; however, the addition of compatibilizer improved the homogeneity of the films, as shown in Figure 3(2A–2C). This behavior is consistent with the literature where it was reported that the use of polymers grafted with maleic anhydride are good compatibilizers for immiscible binary mixtures [13,14,15,16]. Moreover, films with smaller chitosan particle size (Figure 3(3A–3C)) showed better dispersion of the particles of chitosan in the PP matrix, so in these films the formation of agglomerates is almost unnoticeable, which is attributed to the good dispersion of the chitosan particles in the PP matrix.…”
Section: Resultssupporting
confidence: 92%
“…Polyethylene blended with chitosan prepared by melt processing has been reported in numerous publications and has been considered one of the best approaches for preparing materials partially or totally biodegradable because of their high yield and greater control of the final material’s characteristics without atmospheric pollution, in comparison with the solvent evaporation methods [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. Nevertheless, more effort is still required to develop a HDPE blend containing chitosan with improved rheological, thermal, mechanical, morphological and antibacterial.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above mentioned considerations, many researchers are working on blends of chitosan with various polymers either for increasing the bio-based content or for the antimicrobial effect of chitosan. Thus, the development of research about blends of chitosan with polyolefins has received considerable attention, especially those that are prepared by melt processing, because of their high yield, and greater control of the final material’s characteristics without atmospheric pollution, in comparison with the solvent evaporation methods [ 12 , 13 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, there are only a few published reports on blends of chitosan with high density polyethylene (HDPE) [ 38 , 39 ], and, to the best of our knowledge, the compatibilization of these blends with organobentonite synthesized with quaternary ammonium salt impregnated chitosan has not been conducted yet.…”
Section: Introductionmentioning
confidence: 99%